2017
DOI: 10.3390/molecules22101730
|View full text |Cite
|
Sign up to set email alerts
|

NIR Rapid Assessments of Blumea balsamifera (Ai-na-xiang) in China

Abstract: Blumea balsamifera (Ai-na-xiang) is used as an important plant source of natural borneol, which is widely used in the pharmaceutical industry. The aim of this study was to establish the methods based on near infrared (NIR) spectroscopy for determining the geographical origin of B. balsamifera, as well as developing a method for the quantitative rapid analysis of the active pharmaceutical ingredients (APIs). A total of 109 samples were collected from China in 2013 and arbitrarily divided into calibration and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…In patents (Figure B), the trend is similar, but inventions in Energy Technology and Environmental Chemistry related to Industrial Chemistry and Chemical Engineering also show prominently. For example, journal documents using analytical chemistry techniques such as mass spectrometry and nuclear magnetic resonance, infrared, and Raman spectroscopies are augmented with machine learning for use in medical diagnostics, studies of metabolomics, and microbial identification, while biochemistry-related analytical chemistry patents concentrate on the development of analytical devices and methods for use in similar studies. AI-related journal documents with interest in Materials Science and Physical Chemistry discuss topics, such as the evaluation of structure–property relationships in materials by augmenting first-principles calculations with machine learning models, using data from high-throughput experimentation to optimize the properties of functional materials, and the use of published data to enable the discovery of new materials. In patents, the combination of AI, Materials Science, and Physical Chemistry is used in methods for improving semiconductor device fabrication and polymer performance.…”
Section: Distribution Of Ai-related Chemistry Publications By Researc...mentioning
confidence: 99%
“…In patents (Figure B), the trend is similar, but inventions in Energy Technology and Environmental Chemistry related to Industrial Chemistry and Chemical Engineering also show prominently. For example, journal documents using analytical chemistry techniques such as mass spectrometry and nuclear magnetic resonance, infrared, and Raman spectroscopies are augmented with machine learning for use in medical diagnostics, studies of metabolomics, and microbial identification, while biochemistry-related analytical chemistry patents concentrate on the development of analytical devices and methods for use in similar studies. AI-related journal documents with interest in Materials Science and Physical Chemistry discuss topics, such as the evaluation of structure–property relationships in materials by augmenting first-principles calculations with machine learning models, using data from high-throughput experimentation to optimize the properties of functional materials, and the use of published data to enable the discovery of new materials. In patents, the combination of AI, Materials Science, and Physical Chemistry is used in methods for improving semiconductor device fabrication and polymer performance.…”
Section: Distribution Of Ai-related Chemistry Publications By Researc...mentioning
confidence: 99%
“…Noise is included in the NIR spectral data, which is not conducive to the further analysis and processing of signals (Yu et al 2017). In order to obtain the spectral data with high signal to noise ratio and low interference during the establishment of the prediction model, spectral preprocessing is required.…”
Section: Nir Spectroscopy Pretreatmentmentioning
confidence: 99%
“…Borneol (BNL), a simple bicyclic monoterpene, exists widely in the oil of numerous spice berries, including Blumea balsamifera, Artemisia vulgaris, and Gaultheria fragrantissima. , The chiral carbon atom in the structure produces two optical isomers: (+)-borneol (BNL1) and (−)-borneol (BNL2). BNLs exhibit multiple pharmacological properties, including analgesic, antianxiety, antioxidant, and antiinflammation activity. It is reported that BNLs could interfere and inhibit Pgp, which increases the accumulation of drugs in cells. , Nevertheless, the mechanism involved is still unclear.…”
Section: Introductionmentioning
confidence: 99%